Strategi Komunikasi Politik Tim Pemenangan Idris-Imam Pada Pilkada Serentak Di Depok Tahun 2020 - Zahra, Andi Ulfatul; Arsyad, Armin; Nadir, Sakinah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The covid-19 pandemic has had a considerable impact not only in the economic and health sectors but also in the political field, simultaneous regional elections which should have been held in September 2020 but due to the high number of covid-19 cases in Indonesia, it was postponed until December 2020 which made the Idris-Imam winning team required to be more creative because of mass restrictions and limiting direct campaigns so that crowds do not occur and limiting direct campaigns so that new clusters are not formed, This study aims to find out what strategies were carried out by the Idris-Imam successful winning team so that they were able to win the 2020 simultaneous regional elections in Depok City.